Design and Evaluation of Hydrophobic Ion Paired Insulin Loaded Self Micro-Emulsifying Drug Delivery System for Oral Delivery - Jahanzeb Mudassir; Afsheen Raza; Mahtab Ahmad Khan; Huma Hameed; Gamal A. Shazly; Ali Irfan; Sadia Jafar Rana; Khizar Abbas; Muhammad Sohail Arshad; Sajjad Muhammad; Yousef A. Bin Jardan (MDPI AG, 2023)
Despite several novel and innovative approaches, clinical translation of oral insulin delivery into commercially viable treatment is still challenging due to its poor absorption and rapid degradation in GIT. Thus, an insulin-SDS hydrophobic ion pair loaded self-microemulsifying drug delivery system (SMEDDS) was formulated to exploit the hypoglycemic effects of orally delivered insulin. Insulin was initially hydrophobically ion paired with sodium dodecyl sulphate (SDS) to enhance its lipophilicity. The successful complexation of Insulin-SDS was confirmed by FTIR and surface morphology was evaluated using SEM. Stability of insulin after its release from HIP complex was evaluated using SDS PAGE. Subsequently, Ins-SDS loaded SMEDDS was optimized using two factorial designs. In vitro stability of insulin entrapped in optimized SMEDDS against proteolytic degradation was also assessed. Further, antidiabetic activity of optimized Ins-SDS loaded SMEDDS was evaluated in diabetic rats. Insulin complexed with SDS at 6:1 (SDS/insulin) molar ratio with almost five-fold increased lipophilicity. The SMEDDS was optimized at 10% Labraphil M2125 CS, 70% Cremophore EL, and 20% Transcutol HP with better proteolytic stability and oral antidiabetic activity. An Ins-SDS loaded SMEDDS was successfully optimized. Compared with insulin and Ins-SDS complex, the optimized SMEDDS displayed considerable resistance to GI enzymes. Thus, the SMEDDS showed potential for effective delivery of macromolecular drugs with improved oral bioavailability.